A Simple Recipe: the Effect of a Prenatal Nutrition Program on Child Health at Birth - Catherine Haeck; Pierre Lefebvre (Université du Québec à Montréal, École des sciences de la gestion (ESG UQAM), Groupe de recherche sur le capital humain (GRCH), 2016)
We study the impact of a Canadian prenatal nutrition program on child health at birth. The objective of the "oeuf-lait-orange" (eggs-milk-oranges) (OLO) program is to reduce the incidence of prematurity and low birth weight by providing a specific food basket and nutritional guidance to pregnant women in situations of poverty. Our identification strategy exploits exogenous variations in access to the program caused by the progressive implementation of the program. Using detailed administrative birth records for over 1.5 million newborns, we find that the program significantly increased the birth weight of treated children by 69.8 grams and reduced the probability of low birth weight by 3.6 percentage points. We also find that prematurity decreased by 2.2 percentage points and gestation increased by 1.5 days, but these effects are generally not significant. While the cost of the program is equivalent to the comparable United States Supplemental Nutrition Program for Women, Infants and Children (WIC), the food basket is simpler and the gains on birth weight are larger.
Keywords: I12; I18; J13; 330; child health at birth; public program; prenatal nutrition